IMPLEMENTATION OF ACCOUNTING INFORMATION SYSTEM FOR RECEIVABLES IN KASIH IBU WOMEN'S COOPERATIVE - Dewi U. Hadji; Hartati Tuli; Mahdalaena (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Study This aiming For analyze Implementation System Information Accountancy Receivables at the Kasih Ibu Women's Cooperative . This study uses a qualitative descriptive method. The data source used in this study is primary data. This study uses data collection techniques obtained from results interviews , observations and documentation noted in notes field. Research result This show that The Kasih Ibu Women's Cooperative still uses a manual receivables accounting system. So the author offers it in the form of a Cooperative Accounting Information System Application (ASIKK_IT) The use of a manual system is prone to recording errors, with the manual recording process usually taking time, both in recording transactions, calculating interest, and making reports. This cooperative needs to improve the efficiency of recording and managing receivables.